Electrochemical Characterization of Marinobacter atlanticus Strain CP1 Suggests a Role for Trace Minerals in Electrogenic Activity - Onderko, Elizabeth L.; Phillips, Daniel A.; Eddie, Brian J.; Yates, Matthew D.; Wang, Zheng; Tender, Leonard M.; Glaven, Sarah M. (Frontiers in Energy Research, 2019)
The marine heterotroph, Marinobacter atlanticus strain CP1, was recently isolated from the electroautotrophic Biocathode MCL community, named for the three most abundant members: Marinobacter, an uncharacterized member of the Chromatiaceae, and Labrenzia. Biocathode MCL catalyzes the production of cathodic current coupled to carbon fixation through the activity of the uncharacterized Chromatiaceae, renamed as “Candidatus Tenderia electrophaga,” but the contribution of M. atlanticus is currently unknown. Here, we report on the electrochemical characterization of pure culture M. atlanticus biofilms grown under aerobic conditions and supplemented with succinate as a carbon source at applied potentials ranging from 160 to 510 mV vs. SHE, and on three different electrode materials (graphite, carbon cloth, and indium tin oxide). M. atlanticus was found to produce either cathodic or anodic current that was an order of magnitude lower than that of the Biocathode MCL community depending on the oxygen concentration, applied potential, and electrode material. Cyclic voltammetry, differential pulse voltammetry (DPV), and square wave voltammetry (SWV) were performed to characterize putative redox mediators at the electrode surface; however no definitive redox peaks were observed. No effect on current was observed when genes encoding a putative rubredoxin (ACP86_RS07295), as well as a putative NADH:flavorubredoxin oxidoreductase (ACP86_RS07290), were deleted to evaluate their role in EET. The addition of either riboflavin or excess trace mineral solution increased anodic current by ca. an order of magnitude under the conditions in which Biocathode MCL is typically grown. These results indicate that M. atlanticus has a non-negligible ability to utilize electrodes as an electron acceptor, which can be enhanced by the presence of excess trace minerals already available in the growth medium. The ability of M. atlanticus to utilize trace minerals as electron shuttles with extracellular electron acceptors may have broader implications for its natural role in biogeochemical cycling.